Service Quality Dimensions and Members’ Satisfaction: A Mixed-Methods Approach - Yusman, Yacob; Hiram, Ting; Jati Kasuma, Ali (2016)
This study attempts to investigate the relationship between service quality dimensions and satisfaction of credit cooperative members in Sarawak. This study used mixed method approach that involves two phases. The first phase employed a focus group interview to explore the experiences concerning service quality. The result in the first phase is used in the second phase of the study. The second phase of this study uses a quantitative methodology which employs a selfadministered and a cross sectional survey design. 500 copies of questionnaires were distributed to credit cooperative members and 367 usable copies were subsequently collected. Partial least squares structural equation modelling (PLS-SEM) was utilized to assess the effect of service quality dimensions on members’ satisfaction. From the first phase of this study, the researcher has found a new dimension named Personal Interaction in the Service Quality Model. The findings show that assurance, tangibility, reliability, responsiveness and personal interaction have positive effect on members’ satisfaction whereas empathy does not. This study has important implications for policy makers, government and stakeholders of cooperatives for devising appropriate interventions that could enhance the satisfaction of members in credits cooperatives.